Long-term Gain, Short-Term Pain : Assessing the Potential Impact of Structural Reforms in Chile - Santoro, Marika (IMF Working Papers; Working Paper ;, 2015)
In this paper, I study the potential economic impact of the 2015-18 structural reform agenda in Chile, using the IMF dynamic general equilibrium model (GIMF). I find that the agenda has the potential to significantly increase Chile's long-run GDP, although it may have some negative effects in the short term. Ensuring a smooth transition to a higher productive potential depends on three key dimensions: the credibility of the reforms, their effectiveness in closing structural gaps, and their speed of implementation. Badly designed reforms that remove only a very small fraction of the existing structural gaps, at a slow speed, and with little credibility, can greatly reduce the positive impact of the reform agenda on GDP.